Depression and Cognitive Impairment in Disability-Free Early Multiple Sclerosis - Claus G. Haase; Michael Tinnefeld; Marc Lienemann; Reinhard E. Ganz; Pedro M. Faustmann (Behavioural Neurology)
Cognitive and emotional capabilities were evaluated in 73 female patients with stable relapsing-remitting definite, and/or laboratory-supported multiple sclerosis (MS) and were compared with 32 matched healthy controls. Patients were categorized according to their score in the expanded disability status scale (EDSS) to either no (EDSS 0, n = 33) or few clinical signs (EDSS 1–2, n = 40) of MS without physical disability. Patients with EDSS > 0 were characterized by significantly (p These results indicate that depression may present as an early sign in MS followed by cognitive impairment, in particular visuo-spatial short-term memory, before physical disability appears. Neuropsychological tests as mentioned here could serve as early diagnostic tools to detect subtle disease progression and to initiate and monitor disease modifying therapies.